BREAKING BARRIERS IN POST-INDEPENDENCE INDIA a journey out of the northeast. - Falguni, Rajkumar ([S.l.] : ROUTLEDGE, 2023)
This book looks at India of the 1950s and 1960s while it was still emerging from two centuries of colonial rule and striving to come together as a nation. It critically explores the history of nationalism and identity in Northeastern India, a region with diverse ethnolinguistic communities and people, through the personal history of the first Manipuri (Meitei) direct recruit in the Indian Administrative Services. The book weaves in autobiographical stories with the story of Northeast India, capturing its politics, socio-cultural distinctiveness and milieus that set the region apart from the rest of the country. It covers the career of the author in the IAS, serving in Manipur and Karnataka, with the Union Government, and finally as Secretary for the northeastern region. Through these, the book tells the story of a changing society, of a developing nation and a people on the move. It shows how borders and barriers were collapsing and being formed at the same time and how the country was dealing with it. The book is a unique and significant addition to the literature on Manipur; it deepens our understanding of the northeastern states and the complex interactions of the people of the region with the rest of India. Part of the Transitions in Northeastern India series, this book will be of great interest to researchers and scholars of modern history, sociology, social anthropology and postcolonial studies, particularly those concerned with India and Northeast India.
Keywords: Falguni, Rajkumar; Civil service -- India -- History -- 20th century; India, Northeastern -- History -- 20th century; HISTORY / Asia / India & South Asia; SOCIAL SCIENCE / Anthropology / General; SOCIAL SCIENCE / Anthropology / Cultural